YIELD AND QUALITY OF WINTER BARLEY GRAIN DEPENDING ON THE CALCULATED RATES OF MINERAL FERTILIZERS APPLIED TO THE PROGRAMMED YIELD ON DARK GREY PODZOLIC SOILS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Parkhuts, Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The results of studying the influence of the level of mineral fertilizers on the programmed yield of 5.0, 5.5 and 6.0 c/ha of winter barley of Monro variety on dark gray podzolic soils of the Western Forest-Steppe of Ukraine are presented. The content of mobile forms of nitrogen, phosphorus and potassium in dark gray podzolic soil is as follows: according to Tiurin-Kononova, lightly hydrolyzed nitrogen accoynts for 9.2 mg, mobile phosphorus 10.7 mg and exchangeable potassium according to Chirikov 11.6 mg per 100 g of soil. The following options were included in the scheme of the experiment: control ‒ without fertilizers; recommended norm for this zone N60P60K60 (1.00 : 1.00 : 1.00); the calculated norm of fertilizers N77,7P82,2K79,1 (1.00 : 1.06 : 1.02) for the programmed yield of 5.0 t/ha; calculated norm of fertilizers N95,9P98,5K97,0 (1.00 : 1.03 : 1.01) for the programmed yield of 5.5 t/ha; the calculated norm of fertilizers N114,0P114,7K114,8 (1.00 : 1.01 : 1.01) for the programmed yield of 6.0 t/ha. The following coefficients were used for calculations: coefficient of nutrients utilization from soil ‒ N ‒ 30, P2О5 ‒ 10, K2О ‒ 20; nutrients utilization coefficient from mineral fertilizers ‒ N ‒ 80, P2О5 ‒ 40, K2О ‒ 70. The highest yield of 58.1 c/ha with a programmed yield of 6.0 t/ha, on average over the years of research, was obtained by applying the calculated mineral fertilizers in the norm of N114,0P114,7K114,8. The increase in yield in this variant was 2.85 t/ha, or 96.3 %, and to the recommended norm N60P60K60 ‒ 1.30 t/ha. Provided a yield of 4.51 t/ha, which gave an increase in yield to control 1.55 t/ha, or 52.4 %. The lowest yield of winter barley, i.e. 2.96 t/ha, was in the control variant of the experiment ‒ without fertilizers. The highest protein content of 10.9 % and its total yield of 0.63 t/ha was obtained by making the calculated norm in the variant of N114,0P114,7K114,8 for the programmed yield of 6.0 t/ha. In other variants, the protein content was slightly lower, and in the control it was the lowest and was 9.3 % with a total yield of 0.27 t/ha. By introducing the calculated norm of N114,0P114,7K114,8, the highest net profit of 16498 UAH/ha and the level of profitability of 82,6 % was received